'My life is new wave': Poland, Yugoslav new wave and the transnational sense of connectedness in the early 1980s. (27th March 2018) - Jovanovic, Zlatko
Abstract : The article explores the sense of relatedness that the members of the Yugoslav rock music community felt and expressed towards their Polish peers in the period 1981–1982, when the rock scenes in both countries were dominated by the punk/new wave subculture. The article highlights the ways in which Yugoslav and Polish punks were connected to each other through and with the music and seeks to offer a reading that is not reduced to the analysis of political comments concerning the Polish government's suppression of the independent workers' union Solidarity. In doing so, the article stresses different ways in which meanings were produced and communicated in the Yugoslav punk subculture. The analysis is based on rock and youth magazine articles, interviews with prominent members of the Yugoslav rock music culture, and song lyrics. It shows that the punks' subcultural identity played an important role in building the sense of connectedness that Yugoslavs felt towards Polish peers.